Corviale: caduta e salvezza di un’utopia. La città come laboratorio permanente - Briguglio, Fabio; Ferri, Patrizia (Scienze del Territorio, 2015)
To paraphrase “Salvation and fall of  modern art”, a famous essay by Giulio Carlo Argan, today Corviale , as a subject, must be approached from the point of view of a city as an open and permanent laboratory, with the awareness of its essentially problematic nature. That of a place which, from a certain point in time, represents a real work in progress, a fertile ground for experiments and redevelopments which configure it as an open text, sort of a narrative where imageries, conflicts, vital and creative forces converge as much as social tensions do: all ideas for reflection. The possible transformation of a neighbourhood iconic of public housing and social architecture where illegal buildings and participation, drifts of modernity and contemporary potential intertwine, make it controversial but vital, bringing it back to its original singularity;  even though the final sal-vation from an identity marked by closures, separations and by a ruinous destiny, compared to its past, is still far from a collective perspective. In the same time, due to its irreducible original nature, Corviale doesn’t submit itself to a mere survival as “part of the city”, colossal Ufo left to a marginal fate.